Paralelni korpusi i višejezični rječnici - Simeon, Ivana (Array, 2002)
A parallel corpus is a bilingual or multilingual corpus, containing texts written in two or more languages. After they are compiled and processed (which includes correcting errors, segmentation and alignment of corresponding segments), parallel corpora provide a valuable tool for terminological research, contrastive linguistic analysis, determining translation equivalents and are therefore an important resource for bilingual and multilingual lexicography. This paper gives a review of methods for preparation and processing of parallel corpora, as well as their use in multilingual lexicography.